Masson's hemangioma of the larynx: a rare benign vascular lesion in an adult male - Karthikeyan, K.; Narayananan, Lakshmy Arath; Arumugam, Dayanand; V. Segar, Rakshita D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Masson’s hemangioma, also known as intravascular papillary endothelial hyperplasia (IPEH), is a rare benign vascular lesion. IPEH accounts for approximately 2% of vascular tumors and is most frequently reported in the skin and subcutaneous tissues of the head and neck, extremities, and trunk. Although laryngeal hemangiomas are predominantly observed in infants and typically involve the subglottic region, adult laryngeal hemangiomas are uncommon and more often arise in the supraglottic and glottic areas. We report a case of a 50-year-old male who presented primarily with respiratory distress. A tracheostomy had been performed previously to secure the airway. On examination a smooth nodular mass was observed in the medial part of the left aryepiglottic fold, extending to the arytenoid cartilage and post-cricoid region. Radiological evaluation confirmed findings. The patient underwent microlaryngeal excision of the mass. Histopathological examination was suggestive of hemangioma with papillary endothelial hyperplasia (Masson’s hemangioma). This case emphasizes the importance of accurate histopathological evaluation to distinguish this benign entity from malignant vascular tumors. Complete surgical excision remains the treatment of choice and is associated with an excellent prognosis.